2004
DOI: 10.1556/aagr.52.2004.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lignite humic acid on soil nutrient availability at different growth stages of rice grown on Vertisols and Alfisols

Abstract: Field experiments were conducted with rice (ADT-39) during the wet Kharif season (July-October 2001) at two locations, the Tamil Nadu Rice Research Institute (TRRI) farm, Aduthurai (Vertisol) and the Agricultural Research Station (ARS) farm, Pattukkottai (Alfisol), representing the old and new delta areas of the Cauvery, respectively. The same set of treatments was followed in both soils. The treatments consisted of the recommended NPK fertilizer application at 75% and 100% alone, and 10 or 20 kg ha -1 humic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
4
8
0
Order By: Relevance
“…Humalite and peat, on the other hand, had much lower pH values thereby reducing the pH of the amended soils. These findings corroborate those from previous studies (Nandakumar, Sarvanan, Sigaram, & Chandrasekaran, 2004;Sanli et al, 2012). As expected, the blended amendments, BCH and BCP, produced intermediate pH values.…”
Section: Soil Ph and Cation Exchange Capacitysupporting
confidence: 93%
“…Humalite and peat, on the other hand, had much lower pH values thereby reducing the pH of the amended soils. These findings corroborate those from previous studies (Nandakumar, Sarvanan, Sigaram, & Chandrasekaran, 2004;Sanli et al, 2012). As expected, the blended amendments, BCH and BCP, produced intermediate pH values.…”
Section: Soil Ph and Cation Exchange Capacitysupporting
confidence: 93%
“…Sharif et al, (2002) found substantial increases in shoot and root weight of maize by application of humic materials. Also, Nandakumar et al, (2004) found that application of K-humate in combination with N, P and K chemical fertilizers increased availability of soil nutrient at different growth stages of rice.…”
Section: Introductionmentioning
confidence: 98%
“…They have reported 8 to 20 per cent increase in wheat yield, 14 per cent in rice yield, 8 per cent in vegetables and 44 per cent in radish yield with application of HA. Nandakumar (2004) observed higher grain yield of rice with humic acid @ 20 kg ha -1 along with 100 per cent NPK and the per cent increase in grain yield over control was 50.41 and 53.84 per cent in clay loam and sandy loam soils, respectively. Balasubramaniam et al, (2000) reported that the yield attributes viz., grain and stover yield of soybean increased significantly with addition of humic acid @ 20 kg ha -1 to soil along with spraying (0.01 %) at flowering stage.…”
Section: Seed and Straw Yieldmentioning
confidence: 77%